Contractual Relations between Employers and Employees in a Higher Education Institution: Individual and Organisational Outcomes - le Roux, Charles H; Rothmann, Sebastiaan (South African Journal of Higher Education, 2016)
The aim of this study was to investigate the relationship between experiences of contractual relations and job satisfaction, flourishing and turnover intention of employees in a higher education institution. A cross-sectional survey design was used with 300 employees in a higher education institution. The State of the Employment and Psychological Contract Scales, Violation of Psychological Contract Scale, Job Satisfaction Scale, Mental Health Continuum – Short Form and Intention to Quit Scale were administered. The results showed that psychological contract violation, job dissatisfaction and low flourishing (emotional, psychological and social well-being) directly impacted turnover intention. Lack of psychological contract fulfilment indirectly and negatively impacted job satisfaction and flourishing via psychological contract violation. Psychological contract violation indirectly impacted turnover intention via job dissatisfaction and low flourishing of employees in a higher education institution. The results confirmed the importance of psychological contract fulfilment and non-violation for the job satisfaction, flourishing and retention of staff in higher education institutions.